A novel EMT system based on TMR sensors for reconstruction of permeability distribution. (14th September 2018) - Wang, Chao; He, Hanchen; Cui, Ziqiang; Cao, Qingqing; Zou, Ping; Wang, Huaxiang
Abstract: A magnetic catalyst could be applied in a fluidized bed to improve the catalytic efficiency in the methanation and selective hydrogenation processes. Its distributions play an important role in accelerating the reactions. Electromagnetic tomography (EMT) provides an effective solution for online monitoring of the distribution of a magnetic catalyst. However, most of the EMT systems were developed to investigate the conductivity distribution. A novel EMT for the reconstruction of permeability distribution is presented in this paper. The coils, of which the sensitivity are related to frequency and coil size, were used as receivers in conventional EMT systems. In this paper, a tunneling magnetoresistance (TMR) sensor is applied to take the place of the coil. Compared with coils, the advantages of a TMR sensor on the frequency-independence and spatial resolution were investigated. A coil-TMR array was designed, in which the coil geometry was optimized and the TMR sensor was selected. The sensitivity matrix of the novel system was calculated by the perturbation method in a 3D simulation model. A FPGA-based system was designed. The reconstruction results of the magnetic catalyst validated the practicability of the permeability EMT based on TMR sensors.